Pengimplementasian Model Pembelajaran Fun Learning untuk Meningkatkan Minat Belajar di SMPN 3 Reteh - Suroyo, Suroyo; Sianturi, Denggan Tua; Bowen, Rafif Deopra; Khairiyah, Fatinah; Manalu, Klara Debora; Najla, Randu Kinanti; Safitri, Selviana; Nurqasanah, Siti; Sitohang, Tio Pina Uli; Purba, Trido Pasuna (Yayasan Daarul Huda Kruengmane, 2024)
This study explores the implementation of fun learning and ice-breaking activities as effective strategies in enhancing the learning experience in educational settings. Fun learning, combined with ice-breaking techniques, aims to create an engaging and interactive classroom environment that promotes student participation and improves their understanding of the subject matter. The integration of these methods not only reduces anxiety and boredom but also fosters a positive attitude toward learning. By incorporating games, quizzes, and interactive activities, educators can capture students' attention, making complex concepts more accessible and enjoyable. Ice-breaking activities, in particular, are essential at the beginning of lessons to help students relax, build rapport, and encourage collaboration among peers. The study highlights the benefits of this approach, showing that students are more motivated and active in the learning process, leading to better academic outcomes. Moreover, fun learning and ice-breaking techniques cater to diverse learning styles, making education more inclusive and adaptable to different student needs. The findings suggest that adopting these methods can significantly enhance student engagement, retention of information, and overall academic performance. This study advocates for the broader application of fun learning and ice-breaking activities in various educational contexts to create a more dynamic and effective learning environment.